Digital Economy Dynamics: How E-Money, Debit Cards, Inflation, and Exchange Rates Shape Money Demand Stability in Indonesia - Ulfah, Cut Farah; Suriani, Suriani (Grimsa Journal of Business and Economics Studies, 2025)
In the current era, technological advances are developing rapidly, one of which is e-banking through a non-cash payment system that uses APMK (Payment Tools Using Cards) in Indonesia. This study aims to analyze the effect of electronic money, debit cards, inflation, and exchange rates on the stability of money demand in Indonesia and the causal relationship between each variable. This research uses the ARDL (Autoregressive Distributed Lag) model for the period January 2009 - November 2023. The findings show that electronic money has a negative effect on the demand for money in the short term, while in the long term, electronic money has a positive effect on money demand. Debit cards and exchange rates have a positive effect on the demand for money only in the short term. However, inflation has no effect on the demand for money in either the short or long run. There is a two-way causality between the exchange rate and the demand for money, while there is a one-way relationship from debit cards to money demand, from debit cards to electronic money, and from debit cards to exchange rates. The implication of the research is that Bank Indonesia must continue to monitor the use of electronic payment instruments, including debit cards, and estimate their impact on the stability of cash demand and overall monetary policy. Bank Indonesia must also continue to pay attention to price stability when making monetary policy decisions.